KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN POTENSI BERORGANISASI PESERTA DIDIK DI MTS NIHAYATUL AMAL PURWASARI - Aulia Putri; Slamet Sholeh; Khalid Ramadani (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
This study aims to describe and determine the leadership of the madrasah principal in increasing the organizational potential of students at MTs Nihayatul Amal Purwasari. The principal of the madrasa has an important position in mobilizing, activating education, and harmonizing all existing resources in the madrasa. The head of the madrasa as an education manager must be able to build an increase in the organizational potential of students. This study uses a qualitative descriptive method and methods of collecting information in the form of observation, interviews, and documentation. The objectives to be achieved in this study are to find out how the leadership of the madrasah principal in increasing the organizational potential of students at MTs Nihayatul Amal Purwasari and how the planning and implementation of madrasah principals in increasing the organizational potential of students. The results of this study indicate that the head of the madrasah plans programs for students, then discusses with the head of student affairs and teacher mentors to maximize the participant's organizational program and in its implementation students will be directed or fostered according to their interests and talents to increase the potential possessed by students.